Analisis Usahatani dan Saluran Pemasaran Biji Kakao di Kecamatan Juhar Kabupaten Karo Provinsi Sumatera Utara - Antri Sianturi, Meri Juli; Lubis, Zulkarnain; Siregar, Tumpal H.S. (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2020)
This study aims to (1) Know the cost elements of farming; (2) To know the financial feasibility of cocoa farming through analysis of B/C ratio and R/C ratio; (3) to know the cost structure of farming; (4) Analyzing the acceptance and income of cocoa farmers (5) Knowing the cocoa bean marketing system; (6) Knowing the cost, profit, margin and marketing efficiency of each marketing agencies, as well as the large farmer's share obtained by cocoa farmers in Kecamatan Juhar, Karo District.  Determination of location of research conducted by the method of "Purposive Sampling". Sampling conducted by judgment sampling, while the determination of merchant that made the sample was done by snowball sampling method. The research method used in this research is survey method by conducted interviews and observation of fishermen and traders.  The results of this study are 1) The cost of farming cover of labor, fertilizers and pesticides. (2) The result of B/C and R/C ratio is greater than one, so farming can be cultivated because it gives benefits for farmers. (3) The cost of cocoa farming is divided into two, namely: a) Fixed costs and non-fixed costs. The fixed cost (TFC) consists of labor, while the variable cost (VC) consists of fertilizers and pesticides. (4) Average income of cocoa farmers is Rp.13.280.000 per year or equivalent to Rp.1.101.500 per month. (5) Cocoa beans marketing in Juhar Subdistrict there are three types of marketing channels. Marketing channel 1 is Farmers à  Village traders à Sub-district traders à Traders at provincial level. The types of marketing channel II is Farmers à Sub-district traders à Traders at the provincial level. The marketing channel III is Farmers à Village traders à Traders at provincial level. (6) The largest costs, benefits and margins obtained marketing by tipe of one marketing is Rp.2.338; Rp.3.586 dan Rp.5.924 The marketing efficiency is tipe of three marketing yi 4,2%. The bigger the share of the price received by farmers, it can be said that the marketing channel is more efficient. Thus the most efficient marketing channel is the three marketing channels.